The End of Time : The Maya Mystery of 2012 - Aveni, Anthony F. (Book collections on Project MUSE., 2009)
The Internet, bookshelves, and movie theaters are full of prophecies, theories, and predictions that December 21, 2012, marks the end of the world. Award-winning astronomer and Mayan researcher Aveni explores these theories, explains their origins, and measures them objectively against evidence unearthed by Maya archaeologists, iconographers, and epigraphers.